EFFECT OF ABSENTEEISM ON CORPORATE PERFORMANCE: A CASE STUDY OF CADBURY NIGERIA PLC, IKEJA, LAGOS STATE, NIGERIA. - Onikoyi; Adegboyega, Idris; Awolusi; Dele, Olawumi; Michael Ayodeji, Boyede (British Journal of Marketing Studies, 2015)
This study examined the effect of absenteeism on corporate performance. Cadbury Nigeria Plc, Ikeja was used for the case study. The descriptive survey method of research was used and primary data were collected by the used of questionnaire. The primary data collected were processed by the use of statistical package for social sciences (SPSS). Multiple Regression statistical method was used to analyse and test the research hypotheses at 0.05 level of significance. The findings of study showed that there was a significant relationship between Absenteeism and corporate performance. The F test carried out for the model revealed that ?< 0.05 which means the model is statistically significant. Based on the findings, it was recommended that organizations should identify the causes of workers absenteeism and seek means of reducing it, avoid regular hiring and firing of staff, discourage workers from taking irrelevant excuses to be absent from work by ensuring that workers are paid based on the hourly rate system and ensure that staff are motivated by paying them commensurate wage rate that will encourage them to remain on the job and improve their performance.